Permeability of concrete considering the synergetic effect of crack's shape- and size-polydispersities on the percolation. (10th January 2022) - Li, Mingqi; Chen, Huisu; Liu, Lin; Lin, Jianjun; Ullah, Karim
Graphical abstract: Highlights: A new algorithm is proposed to detect whether the inter-oval crack contact or not. Percolation behaviors of polydispersed oval crack are investigated. Coupling effect of shape- and size-polydispersity on percolation is suited. Influence of crack's polydispersity on permeability of fractured concrete is present. Abstract: Crack's shape- and size-polydispersities affect the macro-property of concrete attributed to the changes of microstructure. In particular, the percolation of crack networks causes dramatic changes of concrete's macro-property, such as diffusivity, thermal conductivity and permeability. This work quantitatively captures the percolation thresholds of complex crack networks comprising shape- and size-polydispersed oval cracks, and their effects on the permeability of concrete. Comparing of experimental and numerical data from literature with our results, the reliability of the proposed theoretical framework in this work is verified. The results reveal that the synergistic effect of shape- and size-polydispersities on the percolation threshold can be quantified by introducing an increment to correct the thresholds of polyshaped-monosized crack network. And the influence of the cracks' shape, size-polydispersity on concrete's permeability can be attributed to the effects of the above factors on the percolation threshold as well as surface area of cracks per unit volume of concrete.